PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KUTAI TIMUR - Syardianto . (Jurnal Paradigma (JP), 2017)
The result of research explains the influences among variables. Determinant coefisient number R2 = 0,431 explains that work capability (X1) and work motivation (X2) influence to the employee performance (Y) about 43,1%. From regression model, namely Y= 15.312 + 0,361.X1 + 0,325.X2, both independent variables shape a positive relations to dependent variable. Correlation coefisient zero order/ product moment explain that variable work motivation (X2) has a strong influence to work satisfaction (Y).